A prospective study on the association between social support perceived by parents of children aged 1–7 years and the use of community youth health care services - Fierloos, Irene N.; Windhorst, Dafna A.; Fang, Yuan; Bannink, Rienke; Stam, Marlinda; Slijkerman, Conny A. A.; Jansen, Wilma; Raat, Hein (Frontiers in Public Health, 2022)
Aim This study examined the association between social support perceived by parents of children aged 1–7 years and the use of additional community youth health care services. Methods Data of 749 parents of children aged 1–7 years, gathered in the CIKEO cohort study in the Netherlands, were analyzed. Social support was assessed with the Multidimensional Scale of Perceived Social Support. Data on the use of additional community youth health care services during a period of 1.5 years were obtained from the electronic records of participating youth health care organizations. Multivariable logistic regression models were used to examine the association between perceived social support and the use of additional youth health care services and to explore moderation by the parent's educational level. Results The mean age of the responding parents was 33.9 years (SD = 5.1); 93.6% were mothers. Parents who perceived low to moderate levels of social support had 1.72 (95% CI: 1.11, 2.66) times higher odds of using one or more additional youth health care services during the study period compared to parents who perceived high levels of social support at baseline. This association was independent of predisposing factors, but not independent of need factors (p > 0.05). Furthermore, the association was moderated by the educational level of the parent (p = 0.015). Among parents with a high educational level, low to moderate levels of perceived social support at baseline were associated with 2.93 (95% CI: 1.47, 5.83) times higher odds of using one or more additional youth health care services during the study period independent of predisposing and need factors. Among parents with a low or middle educational level the association between perceived social support and use of additional youth health care services was not significant. Conclusion Our findings provide evidence that low to moderate levels of perceived social support are associated with a higher use of additional community youth health care services among parents of children aged 1–7 years, especially among high educated parents. Recommendations for policy and practice are provided.